Advance model for seismic base isolation Systems of building - Hossein Soleimanloo; Shakeri Soleimanloo (Journal of Applied Sciences and Environmental Management)
Advanced technologies for structural design and construction have the potential for major impact on the bridge and buildings. One of these technologies is base isolation Systems. Numerous of buildings collapses that have occurred in recent earthquakes has exposed the vulnerabilities in existing buildings. Seismic isolation system is achieved via inserting flexible isolator elements into some part of building to increase energy dissipation. This paper investigates and makes recommendations on the structural performance of building using sliding type seismic isolators. First we develop state-of-the-art analytical models. Then, we introduce new models that can consider large deformation effects and the coupling of the vertical and horizontal response during motion simultaneously. We set up some numerical experiment to evaluate our method and compare viability of the two main isolator types (i.e. sliding and elastomeric) for building.